The Emergence Profile of Tree Thinking of Senior High School Students Through the Inquiry Based Learning - Era Mutiara; Aa Juhanda; Billyardi Ramdhan (Universitas Wiralodra, 2020)
The use of tree thinking in learning biology is still rarely used. The purpose of this study was to identify the tree thinking emergence profile of senior high school students through the inquiry-based learning model. This research is using the experimental method. The approach used in this research is a qualitative approach. The population in this study was 36 students of class X in SMA Negeri Sukabumi. The samples were taken by using a purposive sampling technique. The data collection was performed using a written test in the form of LKS by using five tree thinking indicators. The results showed that the value of tree thinking students for the first indicator gained a percentage of 69% included in the good category, the second indicator obtained a percentage of 63% included in the good category, the third indicator received a percentage of 73% included in the good category, the fourth indicator obtained a percentage of 81% included in the very category good, and the fifth indicator gets a percentage of 52% included in the category enough. This result leads to the Student learning outcomes that are categorized as good because the students follow the learning by using models, strategies, and learning approaches that can improve their ability of tree thinking in Arthropoda subjects. This study suggests that the inquiry-based learning model can be used as an alternative in learning biology to improve tree thinking skills.